PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI MEDIASI KEPERCAYAAN KEPADA ATASAN DAN KEPUASAN KERJA (Studi pada Pegawai Tetap Balai Diklat Industri Kementerian Perindustrian Republik Indonesia) - Juniartha, Ida Bagus Made; Wardana, I Made; Wardana, I Made; Putra, Made Surya; Putra, Made Surya (Buletin Studi Ekonomi, 2017)
Abstract: The Effect of Transformational Leadership on Organizational Citizenship Behavior (OCB)with The Mediation of Followers’ Trust in Leader and Job Satisfaction. This study aims to analyze theeffect of transformational leadership on organizational citizenship behavior (OCB) with the mediation offollowers’ trust in leader and job satisfaction. The populations involved in this study are the permanentemployees of Industrial Training Centre of Ministry of Industry, which consisted of 175 employees. Thisresearch sample is equal to population. Furthermore, this study used internet survey method in collectingthe data. A total 175 questionnaires were handed out with a total 148 valid questionnaires for a return rateof 85%. Data are analyzed by using Partial Least square (PLS) with the support of SMARTPLS 2.0software. The results showed that transformational leadership has no effect on OCB, transformationalleadership has a positive effect on follower’s trust in their leader and job satisfaction, follower’s trust intheir leader and job satisfaction has a positive effect on OCB. The findings indicate that the influence oftransformational leadership on OCB is indirect, mediated by the follower’s trust in their leader and jobsatisfaction. Abstrak: Pengaruh Kepemimpinan Transformasional Terhadap Organizational Citizenship Behavior(OCB) dengan Mediasi Kepercayaan kepada Atasan dan Kepuasan Kerja. Tujuan penelitian ini adalahuntuk menganalisis pengaruh kepemimpinan transformasional terhadap organizational citizenshipbehavior (OCB) dengan mediasi kepercayaan kepada atasan dan kepuasan kerja. Populasi pada penelitianini adalah pegawai tetap Balai Diklat Industri Kementerian Perindustrian yang berjumlah 175 orang.Jumlah sampel penelitian ini sama dengan populasi. Lebih lanjut penelitian ini menggunakan metodeinternet survey dalam pengumpulan data. Sebanyak 175 kuesioner disebarkan dan hanya 148 kuesioneryang kembali atau sebesar 85%. Data dianalisis menggunakan Partial Least square (PLS) dengansoftware SMARTPLS 2.0. Hasil penelitian menunjukkan bahwa kepemimpinan transformasional tidakberpengaruh terhadap OCB, kepemimpinan transformasional berpengaruh positif terhadap kepercayaankepada atasan dan kepuasan kerja, kepercayaan kepada atasan dan kepuasan kerja berpengaruh positifterhadap OCB. Hasil temuan mengindikasikan bahwa pengaruh kepemimpinan transformasional terhadapOCB adalah tidak langsung, dimediasi oleh kepercayaan pegawai kepada atasan dan kepuasan kerja.
Keywords: transformational leadership, trust in leader, job satisfaction and organizational citizenship behavior (OCB).